Anjos cansados: o sofrimento de pastores com sintomas da síndrome de burnout na Assembleia de Deus ministério do Belém em São Paulo - Pessoa, Jimmy Barbosa (2020)
This paper aims to analyze the suffering of pastors of the Assembly of God Ministry of Belém in São Paulo, who show symptoms of burnout syndrome. Seeking to understand the consequences in the performance of pastoral work as well as in their personal, social and family life. We present a historical overview of the Assembly of God Church in Brazil and its implantation in the state and in the city of São Paulo, based on institutional historical texts and by historians who start from an academic research on the origin of Assemblies of God in Brazil and on the ground paulistan. We also carried out an analysis on the formation of the pastor, his social profile and the organizational model of AD Belém in São Paulo from the lens of Max Weber and other intellectuals who study Pentecostalism through a sociological proposal. We understand that it is essential to talk about the history and a sociological treatise of the profile of the assembly pastor, for a better understanding of the soil in which this pastor performs his religious functions and has his life linked in all instances of the same, because the pastoral toil implies in the mobilization of the Pentecostal minister as well as his family. We present different theoretical perspectives on the exhaustion syndrome brought by theorists such as: Mézerville, Pereira and Vasconcelos. And we try to carry out a careful analysis of the data collected through the theoretical references used. The methodology of this research followed the field research method through semi-structured interviews with six pastors from ADMB; and there isalso bibliographic research to record necessary and fundamental information for the preparation of chapters of this text. At the conclusion of this research, we point out proposals for caring for pastors based on the results obtained by said analyzes. We believe that the intellectual work carried out for the construction of this Dissertation, is a preparation of the ground for future research on this theme and other themes related to Work Psychology, with a focus on promoting care and treatment in the psychological suffering of leaders of Assemblies of God in Brazil